The Resiliency Of Business Model Innovation Of Indonesian Newspapers During Covid-19 Pandemic - Anton Wachidin Widjaja; Abdullah Sammy (Jurnal Manajemen, 2022)
Newspaper business firms in Indonesia are facing difficult times both in keeping up with the advancement of digital technology and in dealing with the Covid-19 Pandemic. This study attempts to examine the effects of Covid-19 Pandemic, corporate entrepreneurship, and organizational inertia on the business model innovation and business model performance of Indonesian newspaper business firms. This study employs a quantitative method using structural equation modelling (SEM). Data were collected from surveys on 50 newspapers’ leaders in DKI Jakarta, West Java, Central Java, and East Java. This study showed that there were direct consequences of both Covid-19 Pandemic, corporate entrepreneurship, and organizational inertia on business model innovation. Covid-19 Pandemic was also found affecting corporate entrepreneurship. Business model performance as measured by short term performance was not affected by business model innovation. Business model innovation is needed to improve long-term company performance.